Психоаналитический аспект идентификационных стратегий Андрея Ширяева. Трансгрессия культурных кодов русской, казахской и латиноамериканской культур - Фокина, Светлана Александровна (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
In article research is directed to studying the dialogue of A. Shiryaev with a tango phenomenon as semiosis of passion and the Argentinian culture. During the analysis there has been tracked the process of mythologization by poetic consciousness of the poet emigrant of the history of tragic death of the legendary tango performer Carlos Gardel. Reading of author’s connotations is presented to interpretations of an image of the female phantom – madame Ivonne. The basics of psychoanalysis shed light on the poetic text of A. Shiryaev through the prism of the poet’s consciousness and subconscious, respectively, the identification of both Freudian patterns and Jungian archetypes.
Psychoanalytic aspect of Andrey Shiryaev’s identification strategies. Transgression of cultural codes of Russian, Kazakh and Latin American cultures
Keywords: identification; myth; psychoanalysis; madame Ivonne; Gardel